2006
DOI: 10.1001/jama.295.13.jpc60002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Very High-Intensity Statin Therapy on Regression of Coronary Atherosclerosis

Abstract: ClinicalTrials.gov Identifier: NCT00240318.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
1,090
8
64

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 1,862 publications
(1,202 citation statements)
references
References 26 publications
40
1,090
8
64
Order By: Relevance
“…More recent studies have demonstrated that statins are similarly beneficial for the primary and secondary prevention of CVD [10,20,24] and that the relative risk reduction is similar even in patients with very low absolute CV risk [22]. These results are partially explained by intra-vascular ultrasound (IVUS) studies showing that intensive LDL-C lowering using statins can significantly slow, and even reverse, the progression of atherosclerotic plaques in people with coronary heart disease (CHD) [25,26]. Consequently, statins remain the first-line lipid-lowering strategy for the vast majority of people with CV risk, including those with T2D.…”
Section: Statins Are Safe and Effective For The Reduction Of CV Risk mentioning
confidence: 99%
“…More recent studies have demonstrated that statins are similarly beneficial for the primary and secondary prevention of CVD [10,20,24] and that the relative risk reduction is similar even in patients with very low absolute CV risk [22]. These results are partially explained by intra-vascular ultrasound (IVUS) studies showing that intensive LDL-C lowering using statins can significantly slow, and even reverse, the progression of atherosclerotic plaques in people with coronary heart disease (CHD) [25,26]. Consequently, statins remain the first-line lipid-lowering strategy for the vast majority of people with CV risk, including those with T2D.…”
Section: Statins Are Safe and Effective For The Reduction Of CV Risk mentioning
confidence: 99%
“…Denn die Bestimmung der Atheromgröße als neuer Surrogatparameter für die Beurteilung von pharmakodynamischen Defekten hat wesentliche Bedeutung erlangt, nachdem die Entwicklung der Plaquebildung über einen größeren Zeitraum gezeigt hatte, dass nicht nur die Plaqueprogression, sondern auch die Plaqueregression bestimmt werden kann und eng mit der klinischen Symptomatik verbunden ist [8,9,10]. Damit eröffnet der intravaskuläre Ultraschall die Möglichkeit, früher zu erkennen, ob die Wirkung eines Medikaments nicht nur mit Veränderungen von Laborparametern, sondern auch mit einer positiven oder negativen Beeinflussung der koronaren Atherosklerose verbunden ist [11].…”
Section: Fortschritte Der Diagnostik Sind Die Treibende Kraft Für Dieunclassified
“…They observed a plaque reduction of almost 30% by 12 weeks. A human trial of the most effective statin achieved about 6% [2]. The combinedtreatment approach showed a hint of additive effects.…”
mentioning
confidence: 99%